Method for mildly preparing fluorine ion solid electrolyte

By combining specific formulation design with low-temperature annealing process, the problem of large-scale production of fluoride-ion solid electrolytes has been solved, achieving efficient and low-cost mass production with performance comparable to high-energy ball milling, and suitable for all-solid-state fluoride-ion batteries.

CN121439897APending Publication Date: 2026-01-30WUHAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511700113.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-19
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

Existing technologies make it difficult to achieve large-scale production of fluoride ion solid electrolytes. High-energy ball milling results in limited and uneven product quantities, which cannot guarantee the mixing effect and poses safety and cost issues.

Method used

By employing a specific fluoride ion solid electrolyte formulation design and a low-temperature annealing process, and through low-speed ball milling and low-temperature heat treatment at 100~300 ℃, the reaction is promoted to generate more target products, thus achieving the production of kilogram-level fluoride ion solid electrolytes.

Benefits of technology

The production of kilogram-scale fluoride-ion solid electrolytes has been successfully achieved. These electrolytes possess high fluoride-ion conductivity, low electronic conductivity, and a wide electrochemical window, making them suitable for all-solid-state fluoride-ion batteries and expanding their application scope.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121439897A_ABST
    Figure CN121439897A_ABST
Patent Text Reader

Abstract

The invention discloses a method for mildly preparing a fluorine ion solid electrolyte, and belongs to the technical field of fluorine ion batteries. The method comprises the following steps: (1) selecting raw materials in a corresponding stoichiometric ratio according to a chemical formula of the fluorine ion solid electrolyte, and carrying out ball milling treatment on the raw materials to obtain mixed powder; the chemical formula of the fluorine ion solid electrolyte is CsPb < 1-x > M < x > F < 3-x > or RbPb < 1-x > M < x > F < 3-x >, m is Li, Na or K; the value range of x is 0 to 0.7; and (2) carrying out low-temperature heat treatment on the mixed powder at 100-300 DEG C until the reaction is completed to obtain the fluorine ion solid electrolyte. Through the specific formula design and the low-temperature annealing technology, the technology limitation of a traditional method is overcome, kilogram-level product preparation is achieved, and the technology is suitable for large-scale large-batch production. The prepared fluorine ion solid electrolyte has excellent comprehensive performance, and has a wide application prospect in the fields of rechargeable fluorine ion batteries and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fluoride-ion battery technology, and in particular to a mild method for preparing fluoride-ion solid electrolytes. Background Technology

[0002] Since their introduction in late 2011, rechargeable fluoride ion batteries (FIBs) have gained popularity due to their high elemental abundance, low cost, and high efficiency (up to 5000 Wh·L⁻¹). -1 Fluorine-ion batteries, with their theoretical energy density, have become a highly promising energy storage candidate after lithium-ion batteries. Currently developed fluorine-ion electrolytes are mainly divided into liquid electrolytes and ceramic solid-state electrolytes. Liquid electrolytes based on fluorine acceptors suffer from poor interfacial stability, easily leading to the dissolution of active materials, and the use of flammable solvents poses significant safety concerns. Solid-state batteries, due to their higher safety and stability, have become the mainstream research target.

[0003] Currently, the most common method for preparing fluoride-ion solid-state batteries is ball milling. The mainstream approach utilizes the high-energy impact generated during ball milling to grind the material grain size to the nanoscale, while simultaneously introducing crystal defects. Appropriate rotation speed during ball milling is crucial for preparing high-ionic-conductivity fluoride-based solid electrolytes (SEs). High rotation speeds during ball milling ensure uniform mixing of raw materials, which is beneficial for improving ionic conductivity. Higher rotation speeds result in greater impact energy on the material, leading to smaller crystal sizes and even disrupting the crystal structure, generating more defects, including point defects and grain boundaries.

[0004] For example, Chinese invention patent CN113644314A discloses a fluoride ion solid electrolyte material and its preparation method. The chemical formula of this fluoride ion solid electrolyte material is CsPb. 1-x Q x F 3-x Wherein, Q is a metal ion with a valence state of +1, and Q is selected from one or more of K and Rb, where 0 < x ≤ 0.3. The preparation method includes: under an inert atmosphere, mixing and grinding cesium fluoride, lead difluoride, and a fluoride containing Q, followed by ball milling, to obtain a fluoride ion solid electrolyte material. The ball milling is carried out in a planetary ball mill at a speed of 400–800 rpm for 3–50 h, with a ball-to-material ratio of 10:1–50:1. The above-mentioned fluoride ion solid electrolyte material is prepared at room temperature using a high-energy ball milling process.

[0005] In ball milling processes, conventional low-speed planetary ball milling is insufficient to synthesize the target material. For product synthesis, high-energy ball milling is typically employed for the preparation of fluoride ion solid electrolytes, requiring speeds close to or greater than 600 rpm and milling for 6–12 hours or even longer. The degree of sample contamination during ball milling depends on factors such as milling time, speed, the atmosphere surrounding the material, and the hardness differences between the balls. Since ball milling is completed within several hours at high speeds, this method inevitably introduces impurities, adversely affecting the reaction. Furthermore, the material produced using this method is typically in the range of grams to tens of grams, making large-scale production impossible.

[0006] In conclusion, exploring more moderate, and especially more efficient, methods for the large-scale production of fluoride-ion solid electrolytes has become crucial for the development of rechargeable fluoride-ion batteries, and new technological solutions are urgently needed to address the aforementioned issues. Summary of the Invention

[0007] The present invention aims to provide a mild method for preparing fluoride ion solid electrolytes, which can realize the large-scale mass production of fluoride ion solid electrolytes with batch processing capacity reaching the kilogram level, and the performance of the fluoride ion solid electrolytes prepared is comparable to that of products prepared by high-energy ball milling.

[0008] In view of the above-mentioned deficiencies of the prior art, in a first aspect of the present invention, a method for mildly preparing a fluoride ion solid electrolyte is provided, comprising the following steps: (1) Select raw materials with the corresponding stoichiometric ratio according to the chemical formula of the fluoride ion solid electrolyte. The raw materials are ball-milled to obtain mixed powder. The chemical formula of the fluoride ion solid electrolyte is CsPb. 1-x M x F 3-x or RbPb 1-x M x F 3-x M = Li, Na, K; x ranges from 0 to 0.7. (2) The mixed powder is subjected to low-temperature heat treatment at 100~300 ℃ until the reaction is completed to obtain fluoride ion solid electrolyte.

[0009] Preferably, in step (1), the raw material types selected according to the chemical formula of the fluoride ion solid electrolyte include cesium fluoride, rubidium fluoride, lead difluoride, sodium fluoride, potassium fluoride, and lithium fluoride.

[0010] Preferably, in step (1), the ball milling process is carried out under an inert atmosphere.

[0011] Operating under an inert atmosphere helps reduce impurities in the product and optimizes the overall performance of the electrolyte. The formulation design of the fluoride ion solid electrolyte in this application has low oxygen sensitivity and can withstand the effects of unavoidable oxygen introduced during operation and transfer under normal preparation or scale-up conditions.

[0012] Preferably, in step (1), the ball milling speed is 50~500 rpm and the time is 1~4 h.

[0013] Preferably, in step (1), the grinding jar used for ball milling is an agate grinding jar.

[0014] Preferably, in step (1), the ball milling process is carried out in a planetary ball mill.

[0015] Preferably, in step (1), the ball-to-powder ratio in the ball milling process is 5~50:1.

[0016] Preferably, in step (2), the low-temperature heat treatment step includes: placing the mixed powder in a reaction vessel, sealing it, and then placing it in a target temperature environment for treatment.

[0017] In a second aspect of the present invention, a fluoride ion solid electrolyte is provided, which is prepared by the above-described preparation method.

[0018] In a third aspect of the invention, the application of the above-described fluoride ion solid electrolyte is provided, including: its use as a solid electrolyte material in the preparation of all-solid-state fluoride ion batteries.

[0019] The fluoride-ion solid electrolyte prepared using the process of this invention exhibits performance comparable to that prepared by high-energy ball milling. It possesses high fluoride ion conductivity, low electronic conductivity, and a wide electrochemical window, and can be used in all-solid-state fluoride-ion batteries at room temperature, demonstrating promising application prospects.

[0020] Based on the above technical solutions, the design concept and principle of this application are as follows: To achieve the desired synthesis effect, the production of fluoride ion solid electrolytes under traditional process conditions requires high-energy ball milling. High-energy ball milling demands high milling speeds and long processing times. In actual production, excessively high speeds and times result in enormous energy consumption, hindering large-scale production. Furthermore, the high speeds and long processing times lead to high operating costs and compromised safety in scale-up preparations, resulting in small yields, limited to grams or tens of grams per batch. In addition, excessive milling energy causes raw material powder to adhere to the mill jar walls due to the high speed and the presence of grinding beads, requiring external force for removal. This process involves material loss and cannot guarantee uniform powder mixing. In large-scale production, ensuring adequate powder mixing further complicates matters, making it impossible to verify consistency with laboratory results.

[0021] To overcome the limitations of product yield under traditional processes and address the technical problem of synthesis mismatch under scale-up production conditions, this application employs a specific fluoride-ion solid electrolyte formulation design and a low-temperature annealing process. This fluoride-ion solid electrolyte is designed to have low oxygen sensitivity, and the combination of ball milling and low-temperature treatment promotes the forward reaction, generating more of the target product. This process solves the technical problem of incomplete synthesis of the target material under low-speed ball milling by strengthening the bond-to-bond connections or ensuring the presence of a reversible reaction to promote the reaction within this temperature range, thus achieving the synthesis of the target product. Since the raw materials exhibit good reactivity under the above-designed proportions, the pre-milling primarily functions to mix the raw materials. Therefore, this process can be carried out at lower speeds and for shorter durations, overcoming the yield limitations imposed by high-energy ball milling for target product synthesis, as presented in one or more embodiments of this application, ultimately achieving kilogram-scale production of fluoride-ion solid electrolytes.

[0022] It should be noted that the existing technology (CN116169346A) provides a high-ionic-conductivity inorganic solid electrolyte, its preparation method, and its application. This method employs a ball milling process combined with annealing to prepare the inorganic solid electrolyte. In this scheme, the ball-to-material ratio is 10-150:1, the milling speed is 200-600 rpm, and the milling time is 10-50 hours, still falling within the scope of high-energy ball milling processes. The electrolyte actually prepared by this scheme is a lithium-sodium solid-state battery electrolyte, whose conductive ions differ from those in this application, and the reaction mechanism is completely different, exhibiting a fundamental difference from the fluoride-ion solid-state electrolyte system. The purpose of the annealing process in this scheme is to utilize temperature to provide energy, causing the system to evolve towards the stable crystalline phase with the lowest free energy, changing the product's crystalline phase structure, obtaining a long-range ordered crystalline structure, and thus improving the crystallinity of the lithium-sodium solid-state battery electrolyte. As mentioned earlier, the annealing design in this application aims to strengthen the bond-to-bond relationship and complete the reaction of the target phase. This process involves a reversible reaction to promote the reaction within this temperature range, which is necessary. In samples that have not undergone low-temperature heat treatment, the raw materials exist in the form of fluorides rather than the target complex. Furthermore, while increasing the temperature can improve crystallinity to some extent, the primary purpose of the low-temperature heat treatment in this application is to promote product synthesis, which is accompanied by both chemical and physical changes. In summary, the changes and effects of the two annealing methods differ significantly. Moreover, the materials in the aforementioned prior art are sensitive to oxygen, making process control difficult. While practical production at the gram to tens of gram level has been achieved, it is impossible to achieve kilogram-level preparation.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects: This invention provides a method for the mild preparation of fluoride ion solid electrolytes. Through specific formulation design and low-temperature annealing process, it overcomes the process limitations of traditional methods and successfully achieves the preparation of kilogram-level products, which is especially suitable for large-scale mass production.

[0024] This invention provides a fluoride ion solid electrolyte prepared by a mild method for preparing fluoride ion solid electrolytes. It has high fluoride ion conductivity, low electronic conductivity, and a wide electrochemical window, which can be matched with various types of positive and negative electrode materials, thus expanding the application range.

[0025] This invention provides an application of a fluorine-ion solid electrolyte, which has broad application prospects in fields such as rechargeable fluorine-ion batteries. Attached Figure Description

[0026] Figure 1 The fluoride ion solid electrolyte (CsPb) provided in Example 1 0.9 Na 0.1 F 2.9 X-ray diffraction pattern of ) Figure 2 Room temperature impedance diagram of the fluoride ion solid electrolyte provided in Example 1; Figure 3 Cyclic voltammetry curves of the fluoride ion solid electrolyte provided in Example 1; Figure 4 The charge-discharge curve of the fluoride ion solid electrolyte provided in Example 1; Figure 5 The fluoride ion solid electrolyte (CsPb) provided in Example 2 0.8 Na 0.2 F 2.8 X-ray diffraction pattern of ) Figure 6 The room temperature impedance diagram of the fluoride ion solid electrolyte provided in Example 2; Figure 7 Cyclic voltammetry curves of the fluoride ion solid electrolyte provided in Example 2; Figure 8 The charge-discharge curve of the fluoride ion solid electrolyte provided in Example 2; Figure 9 The fluoride ion solid electrolyte (CsPb) provided in Example 3 0.7 Na 0.3 F 2.7 X-ray diffraction pattern of ) Figure 10 The room temperature impedance diagram of the fluoride ion solid electrolyte provided in Example 3; Figure 11 Cyclic voltammetry curves of the fluoride ion solid electrolyte provided in Example 3; Figure 12 The charge-discharge curve of the fluoride ion solid electrolyte provided in Example 3; Figure 13 The fluoride ion solid electrolyte (CsPb) provided in Example 4 0.6 Na 0.4 F 2.6 X-ray diffraction pattern of ) Figure 14 The room temperature impedance diagram of the fluoride ion solid electrolyte provided in Example 4; Figure 15 Cyclic voltammetry curves of the fluoride ion solid electrolyte provided in Example 4; Figure 16 The charge-discharge curve of the fluoride ion solid electrolyte provided in Example 4; Figure 17 The room temperature impedance diagram is for the fluoride ion solid electrolyte provided by the high-energy ball milling method in Comparative Example 1. Detailed Implementation

[0027] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.

[0028] The following are examples of a method for mildly preparing fluoride ion solid electrolytes, comprising the following steps: (1) Based on the chemical formula of fluoride ion solid electrolyte (CsPb) 1-x M x F 3-x or RbPb 1-x M x F 3-x M = Li, Na, K; x ranges from 0 to 0.7. Select raw materials with the corresponding stoichiometric ratios, such as cesium fluoride (rubidium fluoride), lead difluoride, and sodium fluoride (potassium fluoride / lithium fluoride). Weigh them in a planetary ball mill jar according to the stoichiometric ratio in a glove box filled with inert gas, and ball mill them at a rate of 50 to 500 rpm for 1 to 4 hours to obtain a uniform mixed powder. (2) The mixed powder is placed in a reaction vessel and subjected to low-temperature heat treatment at 100~300 °C to obtain a fluoride ion solid electrolyte.

[0029] Example 1 This embodiment provides a mild method for preparing fluoride ion solid electrolytes, the steps of which are as follows: (1) In a glove box under an argon atmosphere, weigh the raw materials according to the stoichiometric ratio of cesium fluoride:lead fluoride:sodium fluoride of 1:0.9:0.1, and weigh a total of 8 mol. Weigh the corresponding mass of agate beads according to the ball-powder ratio of 5:1 and put them into the agate ball milling jar. Then transfer the weighed powder into the agate ball milling jar. After sealing and assembling the planetary ball milling jar in the glove box, remove it from the glove box for ball milling. Ball mill at 100 rpm for 1 h to obtain a uniform mixed powder. (2) The uniformly mixed powder was sealed into the reactor in a glove box and then transferred to a 150 °C oven for low-temperature heat treatment. After heat treatment for 12 h, it was taken out and placed in a glove box to cool, and CsPb was obtained. 0.9 Na 0.1 F 2.9 Electrolyte powder material, namely fluoride ion solid electrolyte.

[0030] In this embodiment, a small amount of fluoride ion solid electrolyte (CsPb) is used. 0.9 Na 0.1 F 2.9 The sample was used for X-ray diffraction testing. Figure 1 CsPb 0.9 Na 0.1 F 2.9 The X-ray diffraction pattern shows that the process successfully synthesized the target product at the kilogram level.

[0031] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A 0.7 mm thick nickel foam was placed on the electrolyte disc, and it was encapsulated using a CR2016 battery case. The total conductivity of the electrolyte material was obtained by measuring the AC impedance at room temperature. See [link to relevant documentation] Figure 2 , Figure 2 The electrolyte impedance diagram provided in this embodiment.

[0032] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A positive electrode (electrolyte:graphite:binder = 6:3:1 coated on carbon-coated aluminum foil) and a negative electrode (PbF2:electrolyte:graphite:binder = 4:4:1:1 coated on lead foil) were prepared. The positive electrode, electrolyte, negative electrode, and 0.7 mm nickel foam were placed sequentially inside a battery case, which was then encapsulated using a CR2016 battery case. A 0.7 mm nickel foam was placed on top of the electrolyte disc, and the battery was encapsulated using a CR2016 battery case. Cyclic voltammetry curves were tested at room temperature to obtain the electrochemical window of the electrolyte material. (See also...) Figure 3 , Figure 3 The cyclic voltammetry curve provided in this embodiment.

[0033] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A positive electrode (coated on carbon-coated aluminum foil using Ag:electrolyte:graphite:binder in a ratio of 4:4:1:1) and a negative electrode (coated on lead foil using PbF2:electrolyte:graphite:binder in a ratio of 4:4:1:1) were prepared. The positive electrode, electrolyte, negative electrode, and 0.7 mm nickel foam were placed sequentially inside a battery case, which was then encapsulated using a CR2016 battery case. The cycle performance of the full cell was tested at room temperature. See also... Figure 4 , Figure 4 The charge / discharge curve provided for this embodiment.

[0034] The above test results show that, under room temperature conditions, its total conductivity is 2.7 × 10⁻⁶. -4 The S / cm and electrochemical window of 3V indicate that the fluoride ion solid electrolyte provided in this embodiment has good conductivity at room temperature and a wide electrochemical window.

[0035] Example 2 This embodiment provides a mild method for preparing fluoride ion solid electrolytes, the steps of which are as follows: (1) In an argon atmosphere glove box, weigh the raw materials according to the stoichiometric ratio of cesium fluoride:lead fluoride:sodium fluoride of 1:0.8:0.2, and weigh a total of 8 mol. Weigh the corresponding mass of agate beads according to the ball-powder ratio of 5:1 and put them into the agate ball mill jar. Then transfer the weighed powder into the agate ball mill jar. After sealing and assembling the planetary ball mill jar in the glove box, remove it from the glove box for ball milling. Ball mill at 100 rpm for 1 h to obtain a uniform mixed powder. (2) The uniformly mixed powder was sealed into the reactor in a glove box and then transferred to a 150 °C oven for low-temperature heat treatment. After heat treatment for 12 h, it was taken out and placed in a glove box to cool, and CsPb was obtained. 0.8 Na 0.2 F 2.8 Electrolyte powder material, namely fluoride ion solid electrolyte.

[0036] In this embodiment, a small amount of fluoride ion solid electrolyte (CsPb) is used. 0.8 Na 0.2 F 2.8 The sample was used for X-ray diffraction testing. Figure 5 CsPb 0.8 Na 0.2 F 2.8 The X-ray diffraction pattern shows that the process successfully synthesized the target product at the kilogram level.

[0037] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A 0.7 mm thick nickel foam was placed on the electrolyte disc, and it was encapsulated using a CR2016 battery case. The total conductivity of the electrolyte material was obtained by measuring the AC impedance at room temperature. See [link to relevant documentation] Figure 6 , Figure 6 The electrolyte impedance diagram provided in this embodiment.

[0038] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A positive electrode (electrolyte:graphite:binder = 6:3:1 coated on carbon-coated aluminum foil) and a negative electrode (PbF2:electrolyte:graphite:binder = 4:4:1:1 coated on lead foil) were prepared. The positive electrode, electrolyte, negative electrode, and 0.7 mm nickel foam were placed sequentially inside a battery case, which was then encapsulated using a CR2016 battery case. A 0.7 mm nickel foam was placed on top of the electrolyte disc, and the battery was encapsulated using a CR2016 battery case. Cyclic voltammetry curves were tested at room temperature to obtain the electrochemical window of the electrolyte material. (See also...) Figure 7 , Figure 7 The cyclic voltammetry curve provided in this embodiment.

[0039] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A positive electrode (coated on carbon-coated aluminum foil using Ag:electrolyte:graphite:binder in a ratio of 4:4:1:1) and a negative electrode (coated on lead foil using PbF2:electrolyte:graphite:binder in a ratio of 4:4:1:1) were prepared. The positive electrode, electrolyte, negative electrode, and 0.7 mm nickel foam were placed sequentially inside a battery case, which was then encapsulated using a CR2016 battery case. The cycle performance of the full cell was tested at room temperature. See also... Figure 8 , Figure 8 The charge / discharge curve provided for this embodiment.

[0040] The results showed that, at room temperature, its total conductivity was 1.7 × 10⁻⁶. -4 The S / cm and electrochemical window of over 3 V indicate that the fluoride ion solid electrolyte provided in this embodiment has good conductivity at room temperature and a wide electrochemical window.

[0041] Example 3 This embodiment provides a mild method for preparing fluoride ion solid electrolytes, the steps of which are as follows: (1) In a glove box under an argon atmosphere, weigh the raw materials according to the stoichiometric ratio of cesium fluoride:lead fluoride:sodium fluoride of 1:0.7:0.3, and weigh a total of 8 mol. Weigh the corresponding mass of agate beads according to the ball-powder ratio of 5:1 and put them into the agate ball milling jar. Then transfer the weighed powder into the agate ball milling jar. After sealing and assembling the planetary ball milling jar in the glove box, remove it from the glove box for ball milling. Ball mill at 100 rpm for 1 h to obtain a uniform mixed powder. (2) The uniformly mixed powder was sealed into the reactor in a glove box and then transferred to a 150 °C oven for low-temperature heat treatment. After heat treatment for 12 h, it was taken out and placed in a glove box to cool, and CsPb was obtained. 0.7 Na 0.3 F 2.7 Electrolyte powder material, namely fluoride ion solid electrolyte.

[0042] In this embodiment, a small amount of fluoride ion solid electrolyte (CsPb) is used. 0.7 Na 0.3 F 2.7 The sample was used for X-ray diffraction testing. Figure 9 CsPb 0.7 Na 0.3 F 2.7 The X-ray diffraction pattern shows that the process successfully synthesized the target product at the kilogram level.

[0043] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A 0.7 mm thick nickel foam was placed on the electrolyte disc, and it was encapsulated using a CR2016 battery case. The total conductivity of the electrolyte material was obtained by measuring the AC impedance at room temperature. See [link to relevant documentation] Figure 10 , Figure 10 The electrolyte impedance diagram provided in this embodiment.

[0044] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A positive electrode (electrolyte:graphite:binder = 6:3:1 coated on carbon-coated aluminum foil) and a negative electrode (PbF2:electrolyte:graphite:binder = 4:4:1:1 coated on lead foil) were prepared. The positive electrode, electrolyte, negative electrode, and 0.7 mm nickel foam were placed sequentially inside a battery case, which was then encapsulated using a CR2016 battery case. A 0.7 mm nickel foam was placed on top of the electrolyte disc, and the battery was encapsulated using a CR2016 battery case. Cyclic voltammetry curves were measured at room temperature to obtain the electrochemical window of the electrolyte material. (See also...) Figure 11 , Figure 11 The cyclic voltammetry curve provided in this embodiment.

[0045] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A positive electrode (coated on carbon-coated aluminum foil using Ag:electrolyte:graphite:binder in a 4:4:1:1 ratio) and a negative electrode (coated on lead foil using PbF2:electrolyte:graphite:binder in a 4:4:1:1 ratio) were prepared. The positive electrode, electrolyte, negative electrode, and 0.7 mm nickel foam were placed sequentially inside a battery case, which was then encapsulated using a CR2016 battery case. The cycle performance of the full cell was tested at room temperature. See also... Figure 12 , Figure 12 The charge / discharge curve provided for this embodiment.

[0046] The results showed that, at room temperature, its total conductivity was 3.4 × 10⁻⁶. -5 The S / cm and electrochemical window of 3 V indicate that the fluoride ion solid electrolyte provided in this embodiment has good conductivity at room temperature and a wide electrochemical window.

[0047] Example 4 This embodiment provides a mild method for preparing fluoride ion solid electrolytes, the steps of which are as follows: (1) In a glove box under an argon atmosphere, weigh the raw materials according to the stoichiometric ratio of cesium fluoride:lead fluoride:sodium fluoride of 1:0.6:0.4, and weigh a total of 8 mol. Weigh the corresponding mass of agate beads according to the ball-powder ratio of 5:1 and put them into the agate ball milling jar. Then transfer the weighed powder into the agate ball milling jar. After sealing and assembling the planetary ball milling jar in the glove box, remove it from the glove box for ball milling. Ball mill at 100 rpm for 1 h to obtain a uniform mixed powder. (2) The uniformly mixed powder was sealed into the reactor in a glove box and then transferred to a 150 °C oven for low-temperature heat treatment. After heat treatment for 12 h, it was taken out and placed in a glove box to cool, and CsPb was obtained. 0.6 Na 0.4 F 2.6 Electrolyte powder material, namely fluoride ion solid electrolyte.

[0048] In this embodiment, a small amount of fluoride ion solid electrolyte (CsPb) is used. 0.6 Na 0.4 F 2.6 The sample was used for X-ray diffraction testing. Figure 13 CsPb 0.6 Na 0.4 F 2.6 The X-ray diffraction pattern shows that the process successfully synthesized the target product at the kilogram level.

[0049] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A 0.7 mm thick nickel foam was placed on the electrolyte disc, and it was encapsulated using a CR2016 battery case. The total conductivity of the electrolyte material was obtained by measuring the AC impedance at room temperature. See [link to relevant documentation] Figure 14 , Figure 14 The electrolyte impedance diagram provided in this embodiment.

[0050] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A positive electrode (electrolyte:graphite:binder = 6:3:1 coated on carbon-coated aluminum foil) and a negative electrode (PbF2:electrolyte:graphite:binder = 4:4:1:1 coated on lead foil) were prepared. The positive electrode, electrolyte, negative electrode, and 0.7 mm nickel foam were placed sequentially inside a battery case, which was then encapsulated using a CR2016 battery case. A 0.7 mm nickel foam was placed on top of the electrolyte disc, and the battery was encapsulated using a CR2016 battery case. Cyclic voltammetry curves were measured at room temperature to obtain the electrochemical window of the electrolyte material. (See also...) Figure 15 , Figure 15 The cyclic voltammetry curve provided in this embodiment.

[0051] The obtained fluoride-ion solid electrolyte was pressed into a 10 mm diameter disc under a pressure of 16 MPa, and its thickness d was measured. A positive electrode (coated on carbon-coated aluminum foil using Ag:electrolyte:graphite:binder in a ratio of 4:4:1:1) and a negative electrode (coated on lead foil using PbF2:electrolyte:graphite:binder in a ratio of 4:4:1:1) were prepared. The positive electrode, electrolyte, negative electrode, and 0.7 mm nickel foam were placed sequentially inside a battery case, which was then encapsulated using a CR2016 battery case. The cycle performance of the full cell was tested at room temperature. See also... Figure 16 , Figure 16 The charge / discharge curve provided for this embodiment.

[0052] The results showed that, at room temperature, its total conductivity was 1.6 × 10⁻⁶. -5 The S / cm and electrochemical window of 3 V indicate that the fluoride ion solid electrolyte provided in this embodiment has good conductivity at room temperature and a wide electrochemical window.

[0053] Example 5 This embodiment provides a mild method for preparing fluoride ion solid electrolytes, the steps of which are as follows: (1) In a glove box under an argon atmosphere, weigh the raw materials according to the stoichiometric ratio of cesium fluoride:lead fluoride:sodium fluoride of 1:0.3:0.7, and weigh a total of 8 mol. Weigh the corresponding mass of agate beads according to the ball-powder ratio of 5:1 and put them into the agate ball milling jar. Then transfer the weighed powder into the agate ball milling jar. After sealing and assembling the planetary ball milling jar in the glove box, remove it from the glove box for ball milling. Ball mill at 100 rpm for 1 h to obtain a uniform mixed powder. (2) The uniformly mixed powder was sealed into the reactor in a glove box and then transferred to a 150 °C oven for low-temperature heat treatment. After heat treatment for 12 h, it was taken out and placed in a glove box to cool, and CsPb was obtained. 0.3 Na 0.7 F 2.3 Electrolyte powder material, namely fluoride ion solid electrolyte.

[0054] Example 6 This embodiment provides a mild method for preparing fluoride ion solid electrolytes, the steps of which are as follows: (1) In an argon atmosphere glove box, weigh the raw materials according to the stoichiometric ratio of cesium fluoride:lead fluoride:sodium fluoride of 1:0.8:0.2, and weigh a total of 8 mol. Weigh the corresponding mass of agate beads according to the ball-to-powder ratio of 5:1 and put them into the agate ball mill jar. Then transfer the weighed powder into the agate ball mill jar. After sealing and assembling the planetary ball mill jar in the glove box, remove it from the glove box for ball milling. Ball mill at 500 rpm for 1 h to obtain a uniform mixed powder; (2) The uniformly mixed powder was sealed into the reactor in a glove box and then transferred to a 150 °C oven for low-temperature heat treatment. After heat treatment for 12 h, it was taken out and placed in a glove box to cool, and CsPb was obtained. 0.8 Na 0.2 F 2.8 Electrolyte powder material, namely fluoride ion solid electrolyte.

[0055] Example 7 This embodiment provides a mild method for preparing fluoride ion solid electrolytes, the steps of which are as follows: (1) In an argon atmosphere glove box, weigh the raw materials according to the stoichiometric ratio of cesium fluoride:lead fluoride:sodium fluoride of 1:0.8:0.2, and weigh a total of 8 mol. Weigh the corresponding mass of agate beads according to the ball-to-powder ratio of 5:1 and put them into the agate ball mill jar. Then transfer the weighed powder into the agate ball mill jar. After sealing and assembling the planetary ball mill jar in the glove box, remove it from the glove box for ball milling. Ball mill at 50 rpm for 1 h to obtain a uniform mixed powder. (2) The uniformly mixed powder was sealed into the reactor in a glove box and then transferred to a 150 °C oven for low-temperature heat treatment. After heat treatment for 12 h, it was taken out and placed in a glove box to cool, and CsPb was obtained. 0.8 Na 0.2 F 2.8 Electrolyte powder material, namely fluoride ion solid electrolyte.

[0056] Example 8 This embodiment provides a mild method for preparing fluoride ion solid electrolytes, the steps of which are as follows: (1) In a glove box under an argon atmosphere, weigh the raw materials according to the stoichiometric ratio of cesium fluoride:lead fluoride:sodium fluoride of 1:0.8:0.2, and weigh a total of 8 mol. Weigh the corresponding mass of agate beads according to the ball-powder ratio of 5:1 and put them into the agate ball milling jar. Then transfer the weighed powder into the agate ball milling jar. After sealing and assembling the planetary ball milling jar in the glove box, remove it from the glove box for ball milling. Ball mill at 100 rpm for 1 h to obtain a uniform mixed powder. (2) The uniformly mixed powder was sealed into the reactor in a glove box, transferred to a tube furnace, and subjected to low-temperature heat treatment at 300 °C for 12 h. After heat treatment, it was taken out and placed in a glove box to cool, and CsPb was obtained. 0.8 Na 0.2 F 2.8 Electrolyte powder material, namely fluoride ion solid electrolyte.

[0057] Comparative Example 1 This comparative example uses high-energy ball milling to process CsPb. 0.9 Na 0.1 F 2.9 CsPb 0.8 Na 0.2 F 2.8 CsPb 0.7 Na 0.3 F 2.7 CsPb 0.6 Na 0.4 F 2.6 The preparation of fluoride ion solid electrolytes was used to compare the performance of products prepared by this process with those prepared by conventional processes.

[0058] In an argon-atmospheric glove box, raw materials were weighed according to a stoichiometric ratio of cesium fluoride:lead fluoride:sodium fluoride of 1:0.9 (0.8, 0.7):0.1, totaling 0.04 mol. Agate beads of the corresponding mass were weighed according to a ball-to-powder ratio of 5:1 and placed into an agate ball mill jar. The weighed powder was then transferred into the agate ball mill jar. The ball mill jar was sealed and assembled in the glove box before being removed and ball milled at 1000 rpm for 8 hours to obtain CsPb. 0.9 Na0.1 F 2.9 Repeat the above steps to obtain CsPb 0.8 Na 0.2 F 2.8 CsPb 0.7 Na 0.3 F 2.7 CsPb 0.6 Na 0.4 F 2.6 Electrolyte powder material.

[0059] After obtaining the electrolyte material, it was pressed into a disc with a diameter of 10 mm under a pressure of 16 MPa, and its thickness d was measured. 0.7 mm of nickel foam was placed on the electrolyte disc, and it was encapsulated using a CR2016 battery case. The total conductivity of the electrolyte material was obtained by testing the AC impedance at room temperature.

[0060] Using the methods and steps described in the above embodiments, CsPb prepared by high-energy ball milling was processed. 0.8 Na 0.2 F 2.8 CsPb 0.7 Na 0.3 F 2.7 CsPb 0.6 Na 0.4 F 2.6 The electrolyte impedance was tested, and the test results are as follows: Figure 17 As shown.

[0061] As demonstrated by the results of the examples and comparative examples, the fluoride-ion solid electrolyte prepared by this process also possesses advantages such as high fluoride ion conductivity, low electronic conductivity, and a wide electrochemical window, comparable to products prepared by high-energy ball milling. It can be matched with various types of positive and negative electrode materials, expanding its application range. Under the condition that the performance meets the usage requirements, this application utilizes a mild method for preparing fluoride-ion solid electrolytes, through specific formulation design and low-temperature annealing, successfully achieving kilogram-level product preparation, representing a significant advancement. This method overcomes the process limitations of traditional high-energy ball milling and is suitable for large-scale mass production.

[0062] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.

Claims

1. A method for the mild preparation of a fluoride ion solid state electrolyte, characterized in that, The method comprises the following steps: (1) selecting raw materials with corresponding stoichiometric ratios according to the chemical formula of the fluorine ion solid electrolyte, ball milling the raw materials to obtain a mixed powder; The chemical formula of the fluoride ion solid electrolyte is CsPb 1-x M x F 3-x or RbPb 1-x M x F 3-x ; M = Li, Na, K; the value range of x is 0-0.7; (2) performing low-temperature heat treatment on the mixed powder at 100-300 DEG C until the reaction is completed to obtain the fluorine ion solid electrolyte.

2. The method of claim 1, wherein: In the step (1), the types of raw materials selected according to the chemical formula of the fluorine ion solid electrolyte include cesium fluoride, rubidium fluoride, lead difluoride, sodium fluoride, potassium fluoride and lithium fluoride.

3. The method of mild preparation of a fluoride ion solid state electrolyte according to claim 1, characterized by: In the step (1), the ball milling is performed in an inert atmosphere.

4. The method for mild preparation of a fluoride ion solid state electrolyte according to claim 1, characterized by: In the step (1), the rotation speed of the ball milling is 50-500 rpm, and the time is 1-4 h.

5. The method of mild preparation of a fluoride ion solid state electrolyte according to claim 1, characterized by: In the step (1), the ball milling tank is an agate ball milling tank.

6. The method of mild preparation of a fluoride ion solid state electrolyte of claim 1, wherein: In the step (1), the ball milling is performed in a planetary ball mill.

7. The method of mild preparation of a fluoride ion solid state electrolyte of claim 1, wherein: In the step (1), the ball milling ratio is 5-50:

1.

8. The method of mild preparation of a fluoride ion solid state electrolyte according to claim 1, wherein, The low-temperature heat treatment comprises the following steps: placing the mixed powder in a reaction kettle, sealing and placing in a target temperature environment for treatment.

9. A fluoride ion solid state electrolyte characterized by: The method is prepared by any one of claims 1-8.

10. Use of a fluoride solid state electrolyte according to claim 9, characterized in that, Comprise: As a solid electrolyte material for preparing a full solid fluorine ion battery.

Citation Information

Patent Citations

  • Fluorine ion solid electrolyte material and preparation method thereof

    CN113644314A

  • High-ionic-conductivity inorganic solid electrolyte and preparation method and application thereof

    CN116169346A